Ancient Skepticism: Pyrrhonism - Machuca, Diego Emanuel (2011)
Pyrrhonism was one of the two main ancient skeptical traditions. In this second paper of the three-part series devoted to ancient skepticism, I present and discuss some of the issues on Pyrrhonian skepticism which have been the focus of much attention in the recent literature. The topics to be addressed concern the outlooks of Pyrrho, Aenesidemus, and Sextus Empiricus.